1980
DOI: 10.1007/bf00137990
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of ocean temperature feedback effects in a coupled carbon-budget energy-balance model for the period 1800?2100

Abstract: The ocean-atmosphere CO: flux in an existing model is reformulated as a function of both surface temperature (SST) and carbon content. The CO 2 model is run in tandem with an energy balance model whose infrared flux to space is modulated by atmospheric CO2 concentration. Global (averaged over latitude and longitude) temperature values obtained from the tandem model are very similar to those produced by simple logarithmic scaling of CO~ concentrations. Simulations indicate the effect of SST feedback is slight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Thus the rate of response of the mixed layer to a change in climate forcing is much faster than that of the full (entire) ocean. Considerations of this fact led several authors, including Jacobson [2002], to ignore the exchange of heat between the mixed layer and the deep ocean [ Schneider and Mass , 1975; Burt and Viecelli , 1980], but Hoffert et al [1980] argue that this term is important in determining the temperature of the mixed layer and lower atmosphere. Hoffert et al [1980] derive the following equation for the globally averaged atmospheric temperature response to forcing: where T a is the temperature of the lower atmosphere, T eq ( t ) is the global average equilibrium temperature for a time‐dependent forcing, h m is the depth of the ocean mixed layer, and θ is the global average potential temperature in the deep ocean as a function of depth.…”
Section: Discussion Of Assumptionsmentioning
confidence: 99%
“…Thus the rate of response of the mixed layer to a change in climate forcing is much faster than that of the full (entire) ocean. Considerations of this fact led several authors, including Jacobson [2002], to ignore the exchange of heat between the mixed layer and the deep ocean [ Schneider and Mass , 1975; Burt and Viecelli , 1980], but Hoffert et al [1980] argue that this term is important in determining the temperature of the mixed layer and lower atmosphere. Hoffert et al [1980] derive the following equation for the globally averaged atmospheric temperature response to forcing: where T a is the temperature of the lower atmosphere, T eq ( t ) is the global average equilibrium temperature for a time‐dependent forcing, h m is the depth of the ocean mixed layer, and θ is the global average potential temperature in the deep ocean as a function of depth.…”
Section: Discussion Of Assumptionsmentioning
confidence: 99%
“…If the first and second terms of (4) are dropped on grounds of small land and atmospheric heat capacity and the last term on the left-hand side on grounds of negligible heat exchange with the deep sea, the formulations of Schneider and Mass [1975] and Burt and Viecelli [1980] are recovered. In what follows, the land heat capacity is considered as sufficiently small to drop the second term in (4), but the atmospheric and deep sea thermal inertia terms are retained.…”
Section: •Ra2[(s/4)(1 -%) -F] = 4•ra2b(teq -Ta)mentioning
confidence: 99%
“…A number of authors have observed that existing data suggest the global mean sea surface, or mixed layer, temperature is of the order of 3 to 5 K warmer than the air temperature of the lower atmosphere (see, e.g., Burt and Viecelli [1980]). Newell and Dopplick [1979] point out that the equatorial sea surface reaches a limiting temperature of about 30øC (303 K) based on the balance between radiative input energy and evaporative loss, compared to equatorial air temperatures in the vicinity of 26øC (see Warren and Schneider's [1979] Table l a for data on the latitudinal distribution of surface air temperature), or about 4 K warmer water than air at low latitudes.…”
Section: World Ocean Heat Budgetmentioning
confidence: 99%
“…Usually they are used independently from one another, although there are feedbacks between temperature and carbon dioxide concentration. Burr and Viecelli [1980] investigated the ocean temperature feedback effects in a coupled carbon budget energy balance model using a diffusion-type ocean for calculating the carbon dioxide distribution and a simple mixed layer ocean for calculating the energy uptake of the ocean. They concluded that there is little advantage in running global CO2 models in tandem with climate models.…”
Section: Introductionmentioning
confidence: 99%